TANGGUNG JAWAB RESIKO DALAM AKAD MUSYAROKAH DAN MUDHARABAH - Sukarno; Triono; Suryanto; Samsudin, Agus Rojak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Musyarakah and Mudharabah contracts are the primary instruments in the Islamic financial system, implementing the profit and loss sharing principle as an alternative to interest-based financing. However, the implementation of risk-sharing responsibilities in these contracts continues to face various challenges in Islamic financial institutions. This study aims to analyze the allocation of risk responsibility in Musyarakah and Mudharabah contracts and compare their implementation from the perspective of Islamic economic law. The study employed a library research method with a descriptive qualitative approach. Data were collected through documentation studies of the Qur'an, Hadith, DSN-MUI Fatwas, the Compilation of Sharia Economic Law (KHES), books, and relevant scientific journals, and were analyzed using the content analysis technique. The findings indicate that, in Musyarakah, losses are borne by the partners in proportion to their respective capital contributions, whereas in Mudharabah, financial losses are borne by the capital owner unless they result from the negligence of the mudharib. This distinction reflects the principle of justice in Islamic economic law. Nevertheless, its implementation still faces challenges, including moral hazard, lack of transparency, and risk transfer practices. Therefore, strengthening the implementation of the risk-sharing principle in accordance with Sharia principles is essential.